Prediksi Jumlah Penduduk di Kabupaten Deli Serdang Menggunakan Metode Regresi Linear Berganda - Damar Ikhsan Nurrobbil; M Farhan Zacky; Prawira Arya Anggara (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
This study aims to predict the total population of Deli Serdang Regency for the year 2025 using a multiple linear regression approach. The data used were obtained from the Central Bureau of Statistics (BPS) of Deli Serdang for the years 2015–2024, with total population as the dependent variable and male population and the percentage of male population as the independent variables. The analysis was carried out through a series of basic assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, all of which indicated that the model met the criteria for a valid regression model. The results of the F-test and t-test showed that both independent variables had a significant influence on the total population. The R² value of 1.000 indicates that the model is capable of explaining 100% of the variation in the population size. Based on the regression model obtained, the projected total population of Deli Serdang in 2025 is estimated to reach 4,075,362 people, an increase of 2,026,882 people from the previous year. These findings are expected to serve as a basis for regional development planning, particularly in the provision of public services and resource management.